Robert B. Parker's Killing the blues - Brandman, Michael; Parker, Robert B., 1932-2010. (New York : G.P. Putnam's Sons, 2011)
Jesse Stone, the chief of police in Paradise, MA, confronts an outbreak of murders.
Keywords: Stone, Jesse (Fictitious character) -- Fiction; City and town life -- Massachusetts -- Fiction; Police chiefs -- Massachusetts -- Fiction